Superalloys 2000 (Ninth International Symposium) 2000
DOI: 10.7449/2000/superalloys_2000_117_126
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of a Damage Tolerant Microstructure for a Nickel Base Turbine Disc Alloy

Abstract: A modified heat treatment has been developed for the nickel-base superalloy, PWA 1113, to create a damage tolerant microstructure @TM) using mechanistic microstructural design concepts. The DTM was designed with the aim of imparting improved fatigue crack growth resistance without forfeiture of other vital properties such as tensile strength, stress rupture life, and low cycle fatigue lifetimes. This was achieved by optimizing the material's grain size, grain boundary morphology, and the intragranular precipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…Traditionally, turbine disks are designed for a finite life using low-cycle fatigue (LCF) criterion under the safe-life design approach. The safe-life approach considers components to be automatically exhausted after 0.1% of the components have initiated a crack of 0.79 mm (1/32 in) in length [1]. However, some premature material damage may occur due to handling, machining damage, fretting, or inherent defects, causing cracks to propagate and become critical during the predicted "safe-life" [2].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, turbine disks are designed for a finite life using low-cycle fatigue (LCF) criterion under the safe-life design approach. The safe-life approach considers components to be automatically exhausted after 0.1% of the components have initiated a crack of 0.79 mm (1/32 in) in length [1]. However, some premature material damage may occur due to handling, machining damage, fretting, or inherent defects, causing cracks to propagate and become critical during the predicted "safe-life" [2].…”
Section: Introductionmentioning
confidence: 99%
“…Past results of researches carried out on PWA1113 have shown that the complex flowery γ ′ morphology was beneficial to improve the mechanical properties. 22,23 Therefore, it is of great importance to study the flowery γ ′ evolution during aging in wrought superalloys.…”
Section: Introductionmentioning
confidence: 99%